Pengaruh Cita Rasa Dan Keragaman Produk Terhadap Keputusan Pembelian Pizza Hut Plaza Asia Tasikmalaya - Aulia Ilham Muhammad; Budhi Wahyu Fitriadi; Kusuma Agdhi Rahwana (Journal of Management and Social Sciences, 2023)
This study aims to determine and analyze the influence of taste and product diversity on purchasing decisions of HUT Pizza for Tasikmalaya HUT Pizza consumers. The method used in this research is quantitative through a survey approach. With a research sample of 100 Tasikmalaya HUT Pizza Consumers. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 29. The results show that Taste has a very good rating classification. Product Diversity has a good rating classification while Purchase Decision has a good classification for Tasikmalaya HUT Pizza Consumers. Together, Product Taste and Diversity have a significant influence on Purchasing Decisions for Tasikmalaya HUT Pizza Consumers. Partially Taste has a significant effect on Purchase Decisions on Tasikmalaya HUT Pizza Consumers, Partially Product Diversity has a significant effect on Purchase Decisions on Tasikmalaya HUT Pizza Consumers